Analisis Faktor-Faktor Yang Mempengaruhi Peningkatan Pendapatan Petani Kelapa Sawit Dari Koperasi Unit Desa Cahaya Sinunukan III Mandailing Natal - Anas Saputra; Sinek Mehuli Br Peranginangin; Polin Ramles (JEMA: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study analyzes the facitors influiencing the income improvement of palm oil farmers in Kopeirasi Uniit Deisa Ciahaya Sinuinukan III, Mandailing Natal. Using quantitative methods and SPSS analysis tools, this research examines two independent variables: the qualiity of cooperative services and the education and training of farmers, against the dependent variable, which is the farmers' income. Diata was colleicted throuigh questiionnaires distribuited to cooperative member farmers. The analysis results show that both independent variables significantly impact the increase in farmers' income. These findings highlight the importance of improving cooperative service quality and providing education and training programs for farmers to enhance their productivity and income. Recommendations are given to the cooperative to strengthen services and develop sustainable training programs. This study contributes to the deveilopment of straitegies for impiroving the welfare of palm oil farmers in rural areas.